Solid electrolyte composite diaphragm and battery
By designing the composite structure of the substrate layer, heat-resistant layer and electrolyte layer in the lithium-ion battery separator, the problems of the separator's heat shrinkage and poor electrolyte wetting at high temperatures are solved, and higher heat resistance and electrochemical performance are achieved .
Patent Information
- Application Number
- CN202420270490.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Utility models(China)
- Current Assignee / Owner
- Filing Date
- 2024-02-01
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2034-02-01
AI Technical Summary
The existing lithium-ion battery separators are prone to heat shrinkage under high temperature conditions, resulting in direct contact between the positive electrode sheet and the negative electrode sheet, causing safety accidents, and their low surface tension makes the electrolyte poor wetting, affecting the performance of the battery.
Develop a solid electrolyte composite membrane, including a substrate layer, a heat-resistant layer and an electrolyte layer, the heat-resistant layer is arranged on the surface of the substrate layer, and the electrolyte layer is arranged on the surface of the heat-resistant layer away from the substrate layer, through this layer structure The design improves the heat resistance and electrochemical properties of the diaphragm.
The solid electrolyte composite separator has excellent heat resistance and thinness, and can maintain a stable structure at high temperatures, avoid direct contact between the positive electrode sheet and the negative electrode sheet of the battery, and improve the safety performance and energy density of the battery.
Smart Images

Figure 00000000_0000_ABST
Abstract
Description
Technical Field
[0001] The utility model relates to a solid electrolyte composite diaphragm and a battery, belonging to the technical field of energy. Background Art
[0002] In recent years, with the continuous development of lithium-ion battery technology, lithium-ion batteries have been widely used in all aspects of human social life. However, safety is an unavoidable focus issue in the large-scale promotion and high-performance development of lithium-ion batteries. Lithium-ion batteries mainly include positive electrodes, negative electrodes and diaphragms, among which the diaphragm is arranged between the positive electrode and the negative electrode, and its main function is to isolate the positive electrode and the negative electrode to prevent the positive electrode and the negative electrode from directly contacting each other and causing a short circuit in the battery, thereby avoiding safety problems such as thermal runaway of the battery. At the same time, the diaphragm has a porous structure, and the porous structure of the diaphragm enables lithium ions to be transmitted between the positive electrode and the negative electrode, so that the lithium-ion battery can work normally.
[0003] At present, the commercial lithium-ion battery separators are mainly polyolefin separators (for example, polyethylene (PE) separators, polypropylene (PP) separators). Polyolefin separators have the advantages of excellent physical and mechanical properties, processability and low cost; but their hot melting temperature is low (for example, the hot melting temperature of PE separators is 135°C, and the hot melting temperature of PP separators is 140°C~160°C). When lithium-ion batteries work under high temperature conditions, polyolefin separators are prone to thermal shrinkage, which causes direct contact between the positive and negative electrodes of lithium-ion batteries and internal short circuits, causing thermal runaway and serious safety accidents, greatly limiting their application in high-performance ion batteries; and the low surface tension of polyolefin separators makes them poorly wettable to electrolytes, which easily increases the internal resistance of lithium-ion batteries, reduces capacity and deteriorates cycle stability.
[0004] In order to solve the above problems, a polyolefin separator is usually used as the substrate layer, and an inorganic modified layer or an organic modified layer is arranged on at least one surface of the substrate layer to improve the thermal properties of the polyolefin separator, thereby improving the cycle performance of the battery. However, even if an inorganic modified layer (for example, an alumina inorganic ceramic material layer) is arranged on at least one surface of the substrate layer or an organic modified layer (PVDF modified layer) is arranged on at least one surface of the substrate layer, it is still impossible to make the separator have both good thermal stability and energy density.
[0005] Therefore, developing highly heat-resistant and lightweight separators to improve the electrochemical performance and safety performance of lithium-ion batteries is of great social and economic significance. Utility Model Content
[0006] The utility model provides a solid electrolyte composite diaphragm. The solid electrolyte composite diaphragm has excellent heat resistance and lightness and thinness, and when applied to a battery, can improve the electrochemical performance and safety performance of the battery.
[0007] The utility model provides a battery, comprising the solid electrolyte composite diaphragm, and the battery has excellent electrochemical performance and safety performance.
[0008] The utility model provides a solid electrolyte composite diaphragm, wherein the solid electrolyte composite diaphragm comprises a substrate layer, a heat-resistant layer and an electrolyte layer;
[0009] The heat-resistant layer is disposed on at least one surface of the substrate layer;
[0010] The electrolyte layer is disposed on a surface of the heat-resistant layer away from the substrate layer.
[0011] or the electrolyte layer is provided on the surface of the substrate layer on which the heat-resistant layer is not provided,
[0012] Alternatively, the electrolyte layer is disposed on both the surface of the heat-resistant layer away from the substrate layer and the surface of the substrate layer not provided with the heat-resistant layer.
[0013] The solid electrolyte composite membrane as described above, wherein the thickness of the solid electrolyte composite membrane is 5.8-21 μm.
[0014] The solid electrolyte composite membrane as described above, wherein the solid electrolyte composite membrane satisfies one of the following:
[0015] a) the thickness of the substrate layer is 5-14 μm;
[0016] b) the thickness of the heat-resistant layer is 0.5-4 μm;
[0017] c) The thickness of the electrolyte layer is 0.3-3 μm.
[0018] The solid electrolyte composite diaphragm as described above, wherein the sum of the thickness of the heat-resistant layer and the thickness of the electrolyte layer is ≤4 μm, and the thickness of the electrolyte layer is ≤ the thickness of the heat-resistant layer.
[0019] The solid electrolyte composite membrane as described above, wherein the porosity of the solid electrolyte composite membrane is 30-70%.
[0020] The solid electrolyte composite diaphragm as described above, wherein the solid electrolyte composite diaphragm further satisfies one of the following conditions:
[0021] a) the porosity of the heat-resistant layer is 20-70%;
[0022] b) The porosity of the substrate layer is 30-70%.
[0023] The solid electrolyte composite diaphragm as described above, wherein the heat-resistant layer is a nanofiber-inorganic nanoparticle composite layer.
[0024] The solid electrolyte composite membrane as described above, wherein the average particle size of the inorganic nanoparticles is 1-200 nm.
[0025] The solid electrolyte composite diaphragm as described above, wherein the substrate layer is a PE diaphragm substrate layer, a PP diaphragm substrate layer or a PE-PP multi-layer composite diaphragm substrate layer.
[0026] The solid electrolyte composite diaphragm as described above, wherein the electrolyte layer is selected from a lithium aluminum titanium phosphate electrolyte layer, a lithium lanthanum zirconium oxygen electrolyte layer, a lithium lanthanum zirconium tantalum oxygen electrolyte layer, a lithium aluminum titanium phosphate-lithium lanthanum zirconium oxygen composite electrolyte layer, a lithium aluminum titanium phosphate-lithium lanthanum zirconium tantalum oxygen composite electrolyte layer or a lithium aluminum titanium phosphate-lithium lanthanum zirconium oxygen-lithium lanthanum zirconium tantalum oxygen composite electrolyte layer.
[0027] The solid electrolyte composite diaphragm as described above, wherein the average particle size of the solid electrolyte in the electrolyte layer is 0.1-1 μm.
[0028] The utility model provides a battery, which comprises the solid electrolyte composite diaphragm as described above.
[0029] The solid electrolyte composite diaphragm of the utility model comprises a substrate layer, a heat-resistant layer and an electrolyte layer. The solid electrolyte composite diaphragm has excellent heat resistance and is relatively thin. When applied to a battery, the energy density of the battery can be improved. The diaphragm is not easy to shrink when heated, which helps to improve the safety performance of the battery.
[0030] The battery of the utility model comprises the solid electrolyte composite diaphragm. During long-term use of the battery, the diaphragm is not easy to shrink, the safety performance is excellent, and the battery also has excellent energy density. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] In order to more clearly illustrate the technical solutions in the embodiments of the present utility model or related technologies, the following briefly introduces the drawings required for use in the embodiments of the present utility model or related technical descriptions. Obviously, the drawings described below are only some embodiments of the present utility model, and for ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.
[0032] Figure 1 This is a schematic structural diagram of a solid electrolyte composite diaphragm in the first embodiment of the utility model;
[0033] Figure 2 This is a schematic structural diagram of a solid electrolyte composite diaphragm in a second embodiment of the present utility model;
[0034] Figure 3 This is a schematic structural diagram of a solid electrolyte composite diaphragm in a third embodiment of the present utility model;
[0035] Figure 4 This is a schematic structural diagram of a solid electrolyte composite diaphragm in a fourth embodiment of the present utility model;
[0036] Figure 5 This is a schematic structural diagram of a solid electrolyte composite diaphragm in a fifth embodiment of the present utility model;
[0037] Figure 6 It is a schematic diagram of the structure of the diaphragm in comparative example 4 of the present invention.
[0038] Description of reference numerals:
[0039] 1: substrate layer;
[0040] 2: Heat-resistant layer;
[0041] 3: electrolyte layer;
[0042] 4: Inorganic modified layer;
[0043] 5: Organic modified layer. DETAILED DESCRIPTION
[0044] The following will be combined with the drawings in the embodiments of the utility model to clearly and completely describe the technical solutions in the embodiments of the utility model. Obviously, the described embodiments are only part of the embodiments of the utility model, not all of the embodiments. Based on the embodiments of the utility model, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the utility model.
[0045] Figure 1 This is a schematic structural diagram of a solid electrolyte composite diaphragm in the first embodiment of the utility model; Figure 2 This is a schematic structural diagram of a solid electrolyte composite diaphragm in a second embodiment of the present utility model; Figure 3 This is a schematic structural diagram of a solid electrolyte composite diaphragm in a third embodiment of the present utility model; Figure 4 This is a schematic structural diagram of a solid electrolyte composite diaphragm in a fourth embodiment of the present utility model; Figure 5 FIG. 1 is a schematic diagram of the structure of a solid electrolyte composite diaphragm in the fifth embodiment of the present invention. Figure 1-5As shown, the first aspect of the utility model provides a solid electrolyte composite membrane, wherein the solid electrolyte composite membrane comprises a substrate layer 1, a heat-resistant layer 2 and an electrolyte layer 3;
[0046] The heat-resistant layer 2 is disposed on at least one surface of the substrate layer 1;
[0047] The electrolyte layer 3 is disposed on the surface of the heat-resistant layer 2 away from the substrate layer 1.
[0048] or the electrolyte layer 3 is provided on the surface of the substrate layer 1 on which the heat-resistant layer 2 is not provided,
[0049] Alternatively, the electrolyte layer 3 is provided on both the surface of the heat-resistant layer 2 away from the base layer 1 and the surface of the base layer 1 on which the heat-resistant layer 2 is not provided.
[0050] In the present invention, the substrate layer 1 is the basis for the solid electrolyte composite diaphragm to work normally, and is used to set the heat-resistant layer 2 and the electrolyte layer 3 to form a solid electrolyte composite diaphragm; the heat-resistant layer 2 refers to a layer with heat-resistant effect known in the art, which can make the solid electrolyte composite diaphragm have excellent thermal stability; the electrolyte layer 3 includes an electrolyte, and the electrolyte layer 3 has excellent lithium ion transmission performance, which helps to reduce the interface resistance between the electrode and the diaphragm, and improve the lithium ion transmission performance between the positive electrode and the negative electrode, thereby reducing the internal resistance of the lithium ion battery, and improving the energy density, cycle stability and low temperature performance of the lithium ion battery.
[0051] In the present invention, the surface of the substrate layer 1 refers to the two surfaces of the substrate layer 1 that are opposite to each other and have the largest area. The heat-resistant layer 2 of the present invention can be arranged on any surface of the substrate layer 1, or on both surfaces of the substrate layer 1; the electrolyte layer 3 can be arranged only on the surface of the heat-resistant layer 2 away from the substrate layer 1, or only on the surface of the substrate layer 1, or respectively on the surface of the heat-resistant layer 2 away from the substrate layer 1 and the surface of the substrate layer 1.
[0052] For example, Figure 1 In the solid electrolyte composite diaphragm shown, the heat-resistant layer 2 is arranged on one surface of the substrate layer 1, and the electrolyte layer 3 is arranged on the surface of the heat-resistant layer 2 away from the substrate layer 1. The solid electrolyte composite diaphragm includes the substrate layer 1, the heat-resistant layer 2 and the electrolyte layer 3 in the stacking direction; in the solid electrolyte composite diaphragm, the heat-resistant layer 2 can provide support and protection, so that the solid electrolyte composite diaphragm is not easy to deform at high temperature, avoiding direct contact between the positive electrode sheet and the negative electrode sheet of the battery and causing a short circuit, thereby preventing the battery from thermal runaway or even catching fire, and the electrolyte layer 3 has a lithium ion conduction function, which can reduce the lithium ion transmission resistance between the solid electrolyte composite diaphragm and the electrode;
[0053] like Figure 2In the solid electrolyte composite membrane shown, the heat-resistant layer 2 is arranged on one surface of the substrate layer 1, and the electrolyte layer 3 is arranged on the other surface of the substrate layer 1. The solid electrolyte composite membrane includes the electrolyte layer 3, the substrate layer 1, and the heat-resistant layer 2 in the stacking direction; in the solid electrolyte composite membrane, the heat-resistant layer 2 has excellent electrolyte adsorption performance, and when it contacts the electrode, the electrode can be fully infiltrated with the electrolyte, and the electrolyte layer has excellent lithium ion transmission performance. Therefore, when the electrolyte layer and the heat-resistant layer 2 are in contact with the electrode sheet of the battery respectively, it is beneficial to reduce the internal resistance of the battery and improve the electrochemical performance of the lithium-ion battery;
[0054] like Figure 3 In the solid electrolyte composite membrane shown, the heat-resistant layer 2 is arranged on one surface of the substrate layer 1, and the electrolyte layer 3 is arranged on the other surface of the substrate layer 1 and the surface of the heat-resistant layer 2 away from the substrate layer 1. The solid electrolyte composite membrane includes the electrolyte layer 3, the heat-resistant layer 2, the substrate layer 1, and the electrolyte layer 3 in the stacking direction; in the solid electrolyte composite membrane, the electrolyte layer 3 is located at the outermost side of the solid electrolyte composite membrane, which can improve the ion transmission resistance between the solid electrolyte composite membrane and the positive electrode sheet of the battery and the solid electrolyte composite membrane and the negative electrode sheet of the battery, which is beneficial to improve the internal resistance of the battery and enhance the electrochemical performance of the battery;
[0055] like Figure 4 In the solid electrolyte composite membrane shown, the heat-resistant layer 2 is respectively arranged on the two surfaces of the substrate layer 1, and the electrolyte layer 3 is arranged on the surface of one of the heat-resistant layers 2 away from the substrate layer 1. The solid electrolyte composite membrane includes the electrolyte layer 3, the heat-resistant layer 2, the substrate layer 1, and the heat-resistant layer 2 in the stacking direction; in the solid electrolyte composite membrane, the heat-resistant layer 2 is respectively arranged on the two surfaces of the substrate layer 1, which can improve the difference in thermal shrinkage tension of the solid electrolyte composite membrane at high temperature, further improve the thermal stability of the solid electrolyte composite membrane, and at the same time help to improve the electrolyte absorption and liquid retention performance of the solid electrolyte composite membrane. The electrolyte layer 3 has a lithium ion conduction function, which can reduce the lithium ion transmission resistance between the solid electrolyte composite membrane and the electrode;
[0056] like Figure 5In the solid electrolyte composite membrane shown, the heat-resistant layer 2 is respectively arranged on the two surfaces of the substrate layer 1, and the electrolyte layer 3 is respectively arranged on the surfaces of the two heat-resistant layers 2 away from the substrate layer 1. The solid electrolyte composite membrane includes the electrolyte layer 3, the heat-resistant layer 2, the substrate layer 1, the heat-resistant layer 2, and the electrolyte layer 3 in the stacking direction; in the solid electrolyte composite membrane, the heat-resistant layer 2 is respectively arranged on the two surfaces of the substrate layer 1, which can improve the difference in thermal shrinkage tension between the two sides of the membrane at high temperature, further improve the thermal stability of the solid electrolyte composite membrane, and at the same time is beneficial to improve the electrolyte absorption and liquid retention performance of the solid electrolyte composite membrane. The electrolyte layer 3 is arranged on the surfaces of the two heat-resistant layers 2 away from the substrate layer 1 (the electrolyte layer 3 is located on the outermost side of the solid electrolyte composite membrane), which can improve the ion transmission resistance between the solid electrolyte composite membrane and the positive electrode sheet of the battery and the solid electrolyte composite membrane and the negative electrode sheet of the battery, which is beneficial to improve the internal resistance of the battery and enhance the electrochemical performance of the battery.
[0057] Therefore, the solid electrolyte composite diaphragm of the utility model including the substrate layer 1, the heat-resistant layer 2 and the electrolyte layer 3 has excellent heat resistance and lightweight characteristics, and when applied to a battery, can improve the electrochemical performance and safety performance of the battery. Specifically, the thermal shrinkage rate of the solid electrolyte composite diaphragm of the utility model in the length direction and the width direction is less than 3% at 150°C.
[0058] In some embodiments of the present invention, when the thickness of the solid electrolyte composite membrane is 5.8-21 μm, the solid electrolyte composite membrane can have both better heat resistance and lightweight characteristics.
[0059] Furthermore, when the solid electrolyte composite diaphragm satisfies one of the following:
[0060] a) the thickness of the substrate layer 1 is 5-14 μm;
[0061] b) The thickness of the heat-resistant layer 2 is 0.5-4 μm;
[0062] c) When the thickness of the electrolyte layer 3 is 0.3-3 μm, the solid electrolyte composite diaphragm can be made thinner while ensuring that each layer can fully play its role, thereby improving the heat resistance of the solid electrolyte composite diaphragm and reducing the internal resistance of the battery.
[0063] In particular, when the sum of the thickness of the heat-resistant layer 2 and the thickness of the electrolyte layer 3 is ≤4μm, and the thickness of the electrolyte layer 3 is ≤ the thickness of the heat-resistant layer 2, the thickness of the solid electrolyte composite membrane can be further reduced, thereby further improving the heat resistance of the solid electrolyte composite membrane while ensuring a lower ion transfer resistance.
[0064] In some embodiments of the present invention, the porosity of the solid electrolyte composite membrane is 30-70%. Wherein, the porosity of the solid electrolyte composite membrane refers to the volume of the pores in the solid electrolyte composite membrane in the total volume of the solid electrolyte composite membrane, that is, the volume percentage of the pores per unit membrane volume. When the porosity of the solid electrolyte composite membrane is within the above range, the solid electrolyte composite membrane not only has excellent mechanical properties, but also has more excellent ion transmission performance.
[0065] Furthermore, when the solid electrolyte composite diaphragm also satisfies one of the following:
[0066] a) The porosity of the heat-resistant layer is 20-70%;
[0067] b) When the porosity of the substrate layer is 30-70%, the mechanical properties and ion transport properties of the solid electrolyte composite membrane can be further improved.
[0068] In some embodiments of the present invention, when the heat-resistant layer 2 is a nanofiber-inorganic nanoparticle composite layer, the heat-resistant layer 2 can have better heat resistance at a thinner thickness.
[0069] The utility model does not specifically limit the nanofibers, and the nanofibers may be commonly used nanofibers in the art. For example, the nanofibers may be selected from at least one of cellulose nanofibers, carboxymethyl cellulose nanofibers, cellulose acetate nanofibers, sulfonated cellulose nanofibers, bacterial cellulose nanofibers, and hydroxyethyl cellulose nanofibers. The utility model does not specifically limit the inorganic nanoparticles, and the inorganic nanoparticles may be commonly used inorganic ceramic particles in the art. For example, the average particle size of the inorganic nanoparticles is 1-200 nm, and the nanomaterials may be fumed alumina.
[0070] In some embodiments, nanofiber materials and inorganic nanoparticle materials can be compounded to obtain a composite layer (heat-resistant layer) with heat-resistant effect. The nanofiber materials in the heat-resistant layer 2 are evenly distributed and stacked in an interlaced manner, so that the nanofiber stacking layer has excellent elasticity, and the thickness of the heat-resistant layer can be effectively controlled and reduced. The nanofiber materials are stacked in an interlaced manner to form a three-dimensional stable framework structure, which provides good high-temperature resistance for the composite diaphragm. The inorganic nanoparticle materials in the heat-resistant layer 2 are filled in the gaps formed by the accumulation of nanofiber materials, thereby increasing the stacking density of the heat-resistant layer, and further making the composite diaphragm have excellent high-temperature performance. Therefore, the heat-resistant layer 2 can be prevented from shrinking at high temperatures. In practical applications, the heat-resistant layer 2 can be tightly bonded to the surface of the substrate layer to play a supporting role, so that the solid electrolyte composite diaphragm does not shrink at high temperatures, maintains the diaphragm structure, and avoids short circuits caused by direct contact between the positive and negative electrodes of the lithium-ion battery, or safety problems such as thermal runaway and fire of the battery caused by direct contact between the positive and negative electrodes. In addition, the heat-resistant layer 2 can also transmit ions and has excellent electrolyte wettability.
[0071] In some embodiments, the heat-resistant layer 2 further includes an adhesive, which can improve the adhesion between the nanofibers and inorganic nanoparticles of the heat-resistant layer 2, increase the density of the coating, and make the heat-resistant layer 2 and the substrate layer 1, and the heat-resistant layer 2 and the electrolyte layer 3 more closely bonded, thereby improving the heat shrinkage resistance of the solid electrolyte composite diaphragm. It is understood that the heat-resistant layer 2 including an adhesive is also known in the art.
[0072] Specifically, the nanofiber-inorganic nanoparticle composite layer may be a nanofiber-inorganic nanoparticle composite layer in a diaphragm of model SU311E99L produced by Shenzhen Xingyuan Material Technology Co., Ltd.
[0073] The present invention does not specifically limit the substrate layer 1, and a commonly used diaphragm substrate in the art can be selected as the substrate layer 1. For example, in some embodiments of the present invention, the substrate layer 1 is a PE diaphragm substrate layer, a PP diaphragm substrate layer, or a PE-PP multi-layer composite diaphragm substrate layer. Among them, the PE-PP multi-layer composite diaphragm substrate layer refers to a multi-layer diaphragm substrate layer formed by compounding a PE layer and a PP layer. The present invention does not limit the number of PE layers and PP layers in the PE-PP multi-layer composite diaphragm substrate layer and the mass proportion of each layer.
[0074] In some embodiments, the PE membrane substrate layer can be a uniaxially stretched PE membrane substrate layer, a biaxially stretched PE membrane substrate layer, or a PE membrane substrate layer prepared by a thermally induced phase separation method, a PE membrane substrate layer prepared by a particle stretching method, a PE membrane substrate layer prepared by a stretching pore-forming method, a PE membrane substrate layer prepared by an electrospinning method, etc.; the PP membrane substrate layer can be a uniaxially stretched PP membrane substrate layer, a biaxially stretched PP membrane substrate layer, or a PP membrane substrate layer prepared by a thermally induced phase separation method, a PP membrane substrate layer prepared by a particle stretching method, a PP membrane substrate layer prepared by a stretching pore-forming method, a PP membrane substrate layer prepared by an electrospinning method, etc.; the PE-PP composite membrane substrate layer can be a PE-PP multi-layer composite membrane substrate layer obtained by stacking any of the above-mentioned PE membrane substrate layers and any of the above-mentioned PP membrane substrate layers, or it can be a PE-PP multi-layer composite membrane substrate layer obtained by co-extrusion.
[0075] The utility model does not specifically limit the electrolyte layer 3, as long as it includes an electrolyte. In some embodiments, the electrolyte layer 3 also includes a binder, a dispersant, and a wetting agent. The utility model does not limit the specific content of the electrolyte, the binder, the dispersant, and the wetting agent in the electrolyte layer 3.
[0076] In some embodiments of the present invention, the electrolyte layer 3 is selected from a lithium aluminum titanium phosphate electrolyte layer, a lithium lanthanum zirconium oxygen electrolyte layer, a lithium lanthanum zirconium tantalum oxygen electrolyte layer, a lithium aluminum titanium phosphate-lithium lanthanum zirconium oxygen composite electrolyte layer, a lithium aluminum titanium phosphate-lithium lanthanum zirconium tantalum oxygen composite electrolyte layer or a lithium aluminum titanium phosphate-lithium lanthanum zirconium oxygen-lithium lanthanum zirconium tantalum oxygen composite electrolyte layer.
[0077] Illustratively, the lithium titanium aluminum phosphate electrolyte layer refers to an electrolyte layer including a lithium titanium aluminum phosphate electrolyte, and the utility model does not limit the specific content of the lithium titanium aluminum phosphate electrolyte in the lithium titanium aluminum phosphate electrolyte layer. The lithium aluminum titanium phosphate-lithium lanthanum zirconium oxygen composite electrolyte layer refers to a composite electrolyte layer that includes both lithium aluminum titanium phosphate and lithium lanthanum zirconium oxygen electrolytes. The utility model does not limit the content of lithium aluminum titanium phosphate and lithium lanthanum zirconium oxygen in the lithium aluminum titanium phosphate-lithium lanthanum zirconium oxygen composite electrolyte layer; the lithium aluminum titanium phosphate-lithium lanthanum zirconium tantalum oxygen composite electrolyte layer refers to a composite electrolyte layer that includes both lithium aluminum titanium phosphate and lithium lanthanum zirconium tantalum oxygen electrolytes. The utility model does not limit the content of lithium aluminum titanium phosphate and lithium lanthanum zirconium tantalum oxygen in the lithium aluminum titanium phosphate-lithium lanthanum zirconium tantalum oxygen composite electrolyte layer; the lithium aluminum titanium phosphate-lithium lanthanum zirconium oxygen-lithium lanthanum zirconium tantalum oxygen composite electrolyte layer refers to a composite electrolyte layer that includes both lithium aluminum titanium phosphate, lithium lanthanum zirconium oxygen electrolyte and lithium lanthanum zirconium tantalum oxygen. The utility model does not limit the content of lithium aluminum titanium phosphate, lithium lanthanum zirconium oxygen and lithium lanthanum zirconium tantalum oxygen in the lithium aluminum titanium phosphate-lithium lanthanum zirconium oxygen-lithium lanthanum zirconium tantalum oxygen composite electrolyte layer.
[0078] In some embodiments of the utility model, when the average particle size of the solid electrolyte in the electrolyte layer 3 is 0.1-1 μm, the thickness of the electrolyte layer can be made thinner, and the flatness and particle packing density of the electrolyte layer can be improved, which is beneficial to increasing the application of the solid electrolyte composite diaphragm in the battery and the interface contact area with the electrode, thereby reducing the internal resistance of the battery.
[0079] In the present invention, the particle size of the solid electrolyte refers to the average particle size of the solid electrolyte.
[0080] The present invention does not limit the preparation method of the solid electrolyte composite diaphragm. In some embodiments, the solid electrolyte composite diaphragm can be prepared by a method comprising the following steps:
[0081] 1) dispersing the nanofiber material and the inorganic particle material in a solvent to obtain a heat-resistant layer coating slurry;
[0082] dispersing the electrolyte in a solvent to obtain an electrolyte layer coating slurry;
[0083] 2) coating the heat-resistant layer coating slurry in step 1) on at least one surface of the substrate layer, and removing the solvent in the substrate layer 1 coated with the heat-resistant layer coating slurry by heat treatment, thereby forming a heat-resistant layer 2 on at least one surface of the substrate layer 1 to obtain an intermediate solid electrolyte composite membrane;
[0084] 3) coating the electrolyte layer coating slurry in step 1) on at least one surface of the intermediate solid electrolyte composite membrane in step 2) (on the surface of the heat-resistant layer away from the substrate layer, and / or on the surface of the substrate layer), and removing the solvent in the intermediate solid electrolyte composite membrane coated with the electrolyte layer coating slurry by heat treatment to obtain a solid electrolyte composite membrane.
[0085] Specifically, in step 1), the binder, nanofibers, and fumed alumina nanomaterials may be uniformly dispersed in deionized water to obtain a heat-resistant layer coating slurry;
[0086] The electrolyte, the binder, the dispersant and the wetting agent may be uniformly dispersed in deionized water to obtain an electrolyte layer coating slurry;
[0087] In step 1), the solid content of the heat-resistant layer coating slurry may be 3% to 40%, and further, the solid content of the heat-resistant layer coating slurry may be 5% to 35%;
[0088] The solid content of the electrolyte layer coating slurry may be 10% to 50%, and further, the solid content of the electrolyte layer coating slurry may be 15% to 45%;
[0089] The coating method of step 2) can be at least one of gravure coating, spray coating and wire rod coating; the heat treatment can be a heating baking treatment.
[0090] The second aspect of the utility model provides a battery, comprising the solid electrolyte composite diaphragm of the first aspect of the utility model.
[0091] It can be understood that the battery of the present invention further includes a positive electrode sheet and a negative electrode sheet, and the solid electrolyte composite diaphragm is placed between the positive electrode sheet and the negative electrode sheet.
[0092] The battery of the utility model has more excellent electrochemical performance and safety performance because it includes the solid electrolyte composite diaphragm of the first aspect.
[0093] The technical solution of the present utility model is described in detail below through specific embodiments.
[0094] Example 1
[0095] The solid electrolyte composite diaphragm of this embodiment is prepared by a method comprising the following steps:
[0096] 1) uniformly dispersing the electrolyte, binder, dispersant and wetting agent in deionized water to obtain an electrolyte layer coating slurry;
[0097] In the electrolyte layer coating slurry, the electrolyte is lithium aluminum titanium phosphate, the binder is SWA610, the dispersant is a 2.5% CMC aqueous solution, and the wetting agent is BYK-ET3004, with a solid content of 30%;
[0098] 2) If Figure 1 As shown, a heat-resistant layer coating slurry is coated on one surface of a substrate layer 1 by gravure coating, and the deionized water in the substrate layer coated with the heat-resistant layer coating slurry is removed by heating and drying, thereby forming a heat-resistant layer 2 on the surface of the substrate layer; then, an electrolyte layer coating slurry is coated on the surface of the heat-resistant layer 2 away from the substrate layer 1 by gravure coating, and the deionized water in the substrate layer coated with the electrolyte layer coating slurry is removed by heating and drying, thereby forming an electrolyte layer 3 on the surface of the heat-resistant layer away from the substrate layer, and obtaining a solid electrolyte composite diaphragm;
[0099] Among them, the porosity of the solid electrolyte composite diaphragm is 38%; the substrate layer 1 is a PE diaphragm substrate layer with a porosity of 38% and a thickness of 9μm; the heat-resistant layer 2 is a nanofiber-inorganic nanoparticle composite layer, in which the average particle size of the inorganic nanoparticles is 30nm, the thickness of the heat-resistant layer is 1.6μm, the porosity is 41%, and the heat-resistant layer is the heat-resistant layer in the diaphragm model SU311E1600L produced by Shenzhen Xingyuan Materials Technology Co., Ltd.; in the electrolyte layer 3, the thickness is 1.5μm, the mass ratio of the electrolyte, adhesive, dispersant and wetting agent is 91.7:7:1:0.3, and the average particle size of the solid electrolyte is 800nm.
[0100] Example 2
[0101] The preparation method of the solid electrolyte composite diaphragm of this embodiment is basically the same as that of embodiment 1, except that:
[0102] 2) If Figure 2 As shown, a heat-resistant layer coating slurry is coated on one surface of a substrate layer 1 by gravure coating, and the deionized water in the substrate layer coated with the heat-resistant layer coating slurry is removed by heating and drying, thereby forming a heat-resistant layer 2 on the surface of the substrate layer; then, an electrolyte layer coating slurry is coated on the other surface of the substrate layer 1 by gravure coating, and the deionized water in the substrate layer coated with the electrolyte layer coating slurry is removed by heating and drying, thereby forming an electrolyte layer 3 on the other surface of the substrate layer, thereby obtaining a solid electrolyte composite diaphragm.
[0103] Example 3
[0104] The preparation method of the solid electrolyte composite diaphragm of this embodiment is basically the same as that of embodiment 1, except that:
[0105] 2) If Figure 3 As shown, the heat-resistant layer coating slurry is coated on one surface of the substrate layer 1 by gravure coating, and the deionized water in the substrate layer coated with the heat-resistant layer coating slurry is removed by heating and drying, thereby forming a heat-resistant layer 2 on the surface of the substrate layer 1; then the electrolyte layer coating slurry is coated on the other surface of the substrate layer and the surface of the heat-resistant layer 2 away from the substrate layer 1 by double-sided coating, and the deionized water in the substrate layer 1 coated with the electrolyte layer coating slurry is removed by heating and drying, thereby forming an electrolyte layer 3 on the other surface of the substrate layer 1 and an electrolyte layer 3 on the surface of the heat-resistant layer 2 away from the substrate layer 1, to obtain a solid electrolyte composite membrane.
[0106] Example 4
[0107] The preparation method of the solid electrolyte composite diaphragm of this embodiment is basically the same as that of embodiment 1, except that:
[0108] 2) If Figure 4 As shown, the heat-resistant layer coating slurry is coated on both surfaces of the substrate layer 1 by double-sided coating, and the deionized water in the substrate layer 1 coated with the heat-resistant layer coating slurry is removed by heating and drying, thereby forming a heat-resistant layer 2 on both surfaces of the substrate layer 1 (the heat-resistant layer is a nanofiber-inorganic nanoparticle composite layer, which is the heat-resistant layer in the diaphragm model SU311E99L produced by Shenzhen Xingyuan Material Technology Co., Ltd.), the heat-resistant layer has a thickness of 0.9μm and a porosity of 41%; then the electrolyte layer coating slurry is coated on the surface of a heat-resistant layer 2 away from the substrate layer 1 by gravure coating, and the deionized water in the substrate layer 1 coated with the electrolyte layer coating slurry is removed by heating and drying, thereby forming an electrolyte layer 3 on the surface of a heat-resistant layer 2 away from the substrate layer 1, and obtaining a solid electrolyte composite diaphragm, in which the electrolyte layer 3 has a thickness of 0.5μm and an average particle size of the solid electrolyte is 300nm.
[0109] Example 5
[0110] The preparation method of the solid electrolyte composite diaphragm of this embodiment is basically the same as that of embodiment 4, except that:
[0111] 2) If Figure 5 As shown, the electrolyte layer coating slurry is coated on the surfaces of the two heat-resistant layers 2 away from the substrate layer 1 by double-sided coating, and the deionized water in the substrate layer 1 coated with the electrolyte layer coating slurry is removed by heating and drying, thereby forming an electrolyte layer 3 on the surfaces of the two heat-resistant layers away from the substrate layer 1 to obtain a solid electrolyte composite diaphragm.
[0112] Comparative Example 1
[0113] The diaphragm of this comparative example is a PE diaphragm with a porosity of 38% and a thickness of 12 μm.
[0114] Comparative Example 2
[0115] The diaphragm of this comparative example is a PP diaphragm with a porosity of 38% and a thickness of 12 μm.
[0116] Comparative Example 3
[0117] The diaphragm of this comparative example is prepared by a method comprising the following steps:
[0118] 1) Evenly dispersing a dispersant, a binder, a fumed alumina nanomaterial (average particle size 30 nm) and a wetting agent in deionized water to obtain an inorganic modified layer coating slurry;
[0119] In the inorganic modified layer coating slurry, the dispersant is 2.5% CMC solution, the binder is LIB-105S, and the wetting agent is BYK-ET3030, and the solid content is 35%;
[0120] 2) coating the inorganic modified layer coating slurry on a functional surface of the substrate layer by gravure coating, and removing deionized water in the substrate layer coated with the inorganic modified layer coating slurry by heating and drying, thereby forming an inorganic modified layer on the functional surface of the substrate layer;
[0121] Among them, the substrate layer is a PE diaphragm substrate layer with a porosity of 38% and a thickness of 9μm; in the inorganic modified layer, the thickness is 3μm, and the mass ratio of the dispersant, adhesive, gas-phase alumina nanomaterial and wetting agent is 3:7:89.6:0.4.
[0122] Comparative Example 4
[0123] The diaphragm of this comparative example is prepared by a method comprising the following steps:
[0124] 1) Dispersing a dispersant, a binder, a fumed alumina nanomaterial (average particle size 30 nm) and a wetting agent uniformly in deionized water to obtain an inorganic modified layer coating slurry;
[0125] Dispersing the dispersant, the binder, the PVDF powder and the wetting agent uniformly in pure water to obtain an organic modified layer coating slurry;
[0126] In the inorganic modified layer coating slurry, the dispersant is 2.5% CMC solution, the binder is LIB-105S, and the wetting agent is BYK-ET3030, and the solid content is 35%;
[0127] In the coating slurry of the organic modified layer, the dispersant is BYK184, the binder is LIB-104, the wetting agent is BYK3034, and the solid content is 35%;
[0128] 2) If Figure 6 As shown, an inorganic modified layer coating slurry is coated on one surface of a substrate layer 1 by gravure coating, and the deionized water in the substrate layer 1 coated with the inorganic modified layer coating slurry is removed by heating and drying, thereby forming an inorganic modified layer 4 on the surface of the substrate layer; an organic modified layer coating slurry is coated on a surface of the inorganic modified layer 4 away from the substrate layer 1 by gravure coating, and the deionized water in the substrate layer 1 coated with the organic modified layer coating slurry is removed by heating and drying, thereby forming an organic modified layer 5 on the surface of the inorganic modified layer 4 away from the substrate layer 1, to obtain a diaphragm;
[0129] Among them, the substrate layer 1 is a PP diaphragm substrate layer with a porosity of 38% and a thickness of 9 μm; in the inorganic modified layer 4, the thickness is 3 μm, and the mass ratio of the dispersant, adhesive, gas-phase alumina nanomaterial and wetting agent is 3:7:89.6:0.4; in the organic modified layer 5, the thickness is 5 μm, and the mass ratio of the dispersant, adhesive, PVDF powder and wetting agent is 6:7:86.6:0.4.
[0130] Test example
[0131] The lithium ion battery is prepared using the separators in the embodiments and comparative examples, specifically comprising:
[0132] 1) Positive electrode
[0133] The positive electrode sheet includes an aluminum foil and a positive electrode active layer arranged on two surfaces of the aluminum foil;
[0134] In the positive electrode active layer, the mass ratio of nickel-cobalt-manganese (NCM 811) ternary positive electrode material, PVDF binder and Super P conductive agent is 90:5:5;
[0135] 2) Negative electrode
[0136] The negative electrode sheet includes a copper foil and a negative electrode active layer arranged on two surfaces of the copper foil;
[0137] In the negative electrode active layer, the mass ratio of graphite negative electrode, SBR binder, CMC cellulose and Super P conductive agent is 90:4:1:5;
[0138] 3) Battery
[0139] The positive electrode sheet of step 1) and the negative electrode sheet of step 2) are baked to remove moisture, and then the positive electrode sheet, the separator and the negative electrode sheet are hot pressed and then wound to obtain an electrode assembly, and the electrode assembly is placed in an aluminum-plastic film, and an electrolyte is injected into the aluminum-plastic film, and a battery is obtained after sealing and forming;
[0140] The electrolyte includes 1M LiPF6, and the solvent is a mixture of EC, EMC and DMC, and the volume ratio of the solvents is 1:1:1.
[0141] Performance Testing
[0142] The separators in the examples and comparative examples were tested in the following 1-2, and the results are shown in Table 1. The batteries in the test examples were tested in the following 3-6, and the results are shown in Table 2.
[0143] 1. SEM test
[0144] The surface morphology of the heat-resistant layer and the surface morphology of the electrolyte layer in the solid electrolyte composite membrane of Example 2 were tested using SEM respectively;
[0145] 2. Heat shrinkage test
[0146] The diaphragms (samples) in the examples and comparative examples were subjected to heat shrinkage tests. The results are shown in Table 1. The test process is as follows:
[0147] At room temperature, cut a sample with a length of 320mm (M0) along the longitudinal direction (MD) and a length of 200mm (T0) along the transverse direction (TD). Then, flatten the sample between two sheets of paper (avoid direct contact between the sample and the hot air in the oven), and then place it in a constant temperature and humidity controlled oven, heat it at 150℃ or 120℃ for 1H, then cool it to the original test conditions, and measure the sample's MD direction length M1 and TD direction length T1. The calculation formula is as follows:
[0148] MD%=(M1-M0) / M0×100%;
[0149] TD%=(T1-T0) / T0×100%.
[0150] 3. Thermal shock performance test
[0151] The lithium-ion battery in the test example is placed at 25°C for 30 minutes, and then transferred to a circulating thermostat. The thermostat is gradually heated to 150°C at 5°C / min. It is kept at 150°C for 10 minutes, and then the test is stopped. During this process, if the lithium-ion battery does not catch fire or explode, it passes this test.
[0152] 4. Rate performance test:
[0153] The lithium-ion battery was left to stand for 48 hours, and then tested on a battery performance test cabinet, and discharged at different rates according to the test requirements.
[0154] 5. Low temperature (-20℃) cycle performance test:
[0155] At -20℃, the lithium-ion battery is charged at a constant current of 1C. When the voltage reaches 4.2V, the charging current is reduced to 0.1C, and the battery continues to charge until the voltage reaches 4.25V. The battery is left standing for 10 minutes. Then, the lithium-ion battery is discharged at a constant current of 1C at -20℃ until the voltage reaches 2.8V. The charging current is reduced to 0.1C, and the battery continues to discharge until the voltage reaches 2.75V. During the charge and discharge conversion, the battery is left standing for 10 minutes, and the above charge and discharge cycle process is repeated 200 times to test the cycle capacity retention rate.
[0156] 6. 25℃ Cycle Performance
[0157] At 25°C, the lithium-ion battery is charged at a constant current of 1C. When the voltage reaches 4.2V, the charging current is reduced to 0.1C, and the charging is continued until the voltage reaches 4.25V. Let it stand for 10 minutes. Then, at 25°C, the lithium-ion battery is discharged at a constant current of 1C until the voltage reaches 2.8V. The charging current is reduced to 0.1C, and the discharge is continued until the voltage reaches 2.75V. During the charge and discharge conversion, the battery is left to stand for 10 minutes, and the above charge and discharge cycle process is repeated 500 times to test the cycle capacity retention rate.
[0158] Table 1
[0159]
[0160] It can be seen from Table 1 that compared with the diaphragm of the comparative example, the solid electrolyte composite diaphragm of the embodiment of the utility model has excellent thermal stability. At 120°C / 1h, the thermal shrinkage of MD and TD are both kept below 0.3%, and at 150°C / 1h, the thermal shrinkage of MD and TD are both kept within 2%, indicating that the solid electrolyte composite diaphragm of the embodiment of the utility model is not easy to deform at high temperature, which is beneficial to improving the safety performance of lithium-ion batteries.
[0161] Table 2
[0162]
[0163] It can be seen from Table 2 that the lithium-ion battery prepared using the solid electrolyte composite diaphragm of the utility model can withstand a high temperature thermal shock test at 150°C, and the low temperature (-20°C) cycle performance and 25°C cycle performance of the battery are significantly improved.
[0164] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the utility model, rather than to limit it. Although the utility model has been described in detail with reference to the aforementioned embodiments, ordinary technicians in this field should understand that they can still modify the technical solutions recorded in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not make the essence of the corresponding technical solution deviate from the scope of the technical solution of the embodiments of the utility model.
Claims
1. A solid electrolyte composite diaphragm, characterized in that: The solid electrolyte composite diaphragm comprises a substrate layer, a heat-resistant layer and an electrolyte layer; The heat-resistant layer is disposed on at least one surface of the substrate layer; The electrolyte layer is disposed on a surface of the heat-resistant layer away from the substrate layer. or the electrolyte layer is provided on the surface of the substrate layer on which the heat-resistant layer is not provided, Alternatively, the electrolyte layer is disposed on both the surface of the heat-resistant layer away from the substrate layer and the surface of the substrate layer not provided with the heat-resistant layer.
2. The solid electrolyte composite diaphragm according to claim 1, characterized in that: The thickness of the solid electrolyte composite membrane is 5.8-21 μm.
3. The solid electrolyte composite diaphragm according to claim 2, characterized in that: The solid electrolyte composite diaphragm satisfies one of the following: a) the thickness of the substrate layer is 5-14 μm; b) the thickness of the heat-resistant layer is 0.5-4 μm; c) The thickness of the electrolyte layer is 0.3-3 μm.
4. The solid electrolyte composite diaphragm according to claim 3, characterized in that: The sum of the thickness of the heat-resistant layer and the thickness of the electrolyte layer is ≤4 μm, and the thickness of the electrolyte layer is ≤ the thickness of the heat-resistant layer.
5. The solid electrolyte composite diaphragm according to any one of claims 1 to 4, characterized in that: The porosity of the solid electrolyte composite membrane is 30-70%.
6. The solid electrolyte composite diaphragm according to claim 5, characterized in that: The solid electrolyte composite membrane also satisfies one of the following: a) the porosity of the heat-resistant layer is 20-70%; b) The porosity of the substrate layer is 30-70%.
7. The solid electrolyte composite diaphragm according to any one of claims 1 to 4, characterized in that: The heat-resistant layer is a nanofiber-inorganic nanoparticle composite layer.
8. The solid electrolyte composite diaphragm according to claim 7, characterized in that: The average particle size of the inorganic nanoparticles is 1-200 nm.
9. The solid electrolyte composite diaphragm according to any one of claims 1 to 4, characterized in that: The substrate layer is a PE diaphragm substrate layer, a PP diaphragm substrate layer or a PE-PP multi-layer composite diaphragm substrate layer.
10. The solid electrolyte composite diaphragm according to any one of claims 1 to 4, characterized in that: The electrolyte layer is selected from lithium titanium aluminum phosphate electrolyte layer, lithium lanthanum zirconium oxygen electrolyte layer, lithium lanthanum zirconium tantalum oxygen electrolyte layer, lithium titanium aluminum phosphate-lithium lanthanum zirconium oxygen composite electrolyte layer, lithium titanium aluminum phosphate-lithium lanthanum zirconium tantalum oxygen composite electrolyte layer or lithium titanium aluminum phosphate-lithium lanthanum zirconium oxygen-lithium lanthanum zirconium tantalum oxygen composite electrolyte layer.
11. The solid electrolyte composite diaphragm according to any one of claims 1 to 4, characterized in that: The average particle size of the solid electrolyte in the electrolyte layer is 0.1-1 μm.
12. A battery, characterized in that: The invention comprises the solid electrolyte composite diaphragm as described in any one of claims 1 to 11.